Chemical composition of brown and red algae from Kelapa Beach, Tuban, East Java and their potential as ruminant feed - Hidayah, N.; Maulina, N. W.; Noviandi, C. T.; Astuti, A.; Dono, N. D.; Kustantinah, Kustantinah (2022)
This research was designed to evaluate the nutrient content of brown (Laminaria Sp. and Padina australis) and red algae (Eucheuma cottonii and Gracilaria Sp.) from Kelapa beach, Tuban, East Java. The algae were cleaned from dirt and other materials before drying under the sun. All of the algae were ground and analyzed using proximate analysis (dry matter (DM), ash, organic matter (OM), ether extract (EE), crude protein (CP), crude fiber (CF), and nitrogen-free extract (NFE)) and gross energy with a bomb calorimeter. Data were analyzed descriptively by calculating the average of data obtained. The result showed that brown algae of Padina australis had the highest DM (30.59%) and CP (12.57%). The red algae of Eucheuma cottonii had the highest OM (76.58%), EE (2.85%), CF (8.80%), NFE (56.38%), and gross energy (2,911 Cal/g) but had the lowest DM (13.67%) and CP (8.55%). In opposite with Gracilaria sp. had the highest ash (65.63%) and the lowest OM (34.37%), EE (0.21%), CF (2.49%), NFE (19.95%) and gross energy (1,083 Cal/g). Based on this study, brown algae (Laminaria sp and Padina australis) and red algae (Eucheuma cottonii and Gracilaria sp.) have the potential as ruminant feed, especially as mineral and soluble carbohydrate sources.